The effect of aqua-therapy on plasma and interleukin-12 and 17 in patients with multiple sclerosis - Nejatpour, S.; Fathei, M.; Yaghoubi, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Cytokines such as Interleukin 12 (IL-12) and Interleukin 17(IL-17) influence the function of the immune system and different tissues and are studied due to the role they play in Multiple Sclerosis (MS). The aim of the study was to investigate the effect of aqua-therapy on plasma IL-12 and IL-17 in patients with MS. 25 men with MS were divided into two groups: exercise and control. Blood sample was taken before and after the intervention protocol. The exercise group carried out three exercise sessions per week during eight weeks. The beginning and final parts of each session included warming up and cool down, and were carried out in shallow areas. These activities were designed and implemented by a researcher under the supervision of a sports physiologist and an experienced neurologist. During the training sessions, the first 10 minutes were for warming up, and the last 5 minutes of training were for cool down. Exercise intensity was approximately 75% of heart rate reserve. The data demonstrated that both IL-12 and IL-17 decreased significantly from pre-test to post-test in the exercise group. We conclude that aqua-training may reduce risk factors regarding multiple sclerosis, including IL-12 and IL-17.